Biochemical Investigation into the Benefit of Quercetin Supplementation in Hypoxic Mice - Otomewo LO; Anthony TE; Moke EG; Onohwosafe J (Ibom Medical Journal)
Context: Since the proper flow of oxygen into the human body signifies one of the core features of living organisms, a shortage in supply poses a significant threat to survival. Objective: This study aimed to investigate the effects of intermittent hypoxia on mice and the benefit of pre-administered quercetin on such effects.